Pengaruh Nasi Bayam Terhadap Minat Anak Mengkonsumsi Makanan Sehat Usia 5-6 Tahun di PAUD Ceria Kubu Raya - Putri, Wahyu Tri Nabella; Miranda, Dian; Perdina, Siska (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The background of this study is based on children's low interest in consuming vegetables, especially spinach, even though vegetables play an important role in children's growth and development. This study aims to determine the effect of spinach rice on the interest of 5-6-year-old children in consuming healthy foods at the Ceria Kubu Raya Early Childhood Education Center. This study uses a quantitative approach with a one-group pretest-posttest experimental design. The research subjects consisted of 30 children selected using simple random sampling. Data collection was conducted through observation and documentation. Data analysis was performed using simple linear regression tests. Data calculations were performed using SPSS Statistics 26 software. The research results show a significant increase in children's interest after being given a presentation of spinach rice, indicated by the t-test results (t-count = 13.873; significance 0.000 < 0.05). The appealing presentation of spinach rice, combined with side dishes that children like, along with support from teachers, has proven to be effective in increasing children's interest in consuming healthy food. This study provides important contributions to the development of strategies for presenting nutritious food that is appealing to young children.